2020
DOI: 10.1007/s12662-020-00688-1
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity exercise programs in people with dementia — a systematic review and meta-analysis

Abstract: Dementia is a syndrome characterized by a progressive deterioration of cognitive and physical functions. The aim of this systematic review was to investigate the effects of high-intensity exercise training (HIT) programs on cognitive and mental health, physical performance, activities of daily living (ADLs) and quality of life (QoL) in people with dementia. A systematic literature search for randomized controlled trials was performed until July 2019. We calculated mean difference (MD) or standardized MD (SMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…One systematic review 45 Adults with depression n=11 63 64 66-73 75 Dementia n=5 [107][108][109][110][111] Older adults n=5 [33][34][35][36][37] Chronic obstructive pulmonary disease n=4 78 112-114 Multiple sclerosis n=4 81 115-117 Pregnant or postnatal or post-partum women n=4 [38][39][40][41] Adults with various chronic diseases n=3 [118][119][120] Apparently healthy adults n=3 [42][43][44] Anxiety disorders n=3 84 85 121 Cardiovascular disease n=3 80 122 123 Older adults with depression n=4 63 65 74 124 Renal disease n=3 86 125 126 Stroke n=3 21 127 128 Arthritis and rheumatic diseases n=2 82 129 130 Cognitive impairment n=2 77 131 HIV/AIDS n=2 76 132 Post-traumatic stress disorder n=2 133 134 Various mental health disorders n=2 83 135 Fatigue n=1 136 Knee osteoarthritis n=1 129 Neurological disorders n=1 137 Schizophrenia n=1 138 Substance use disorder n=1 79…”
Section: Psychological Distressmentioning
confidence: 99%
“…One systematic review 45 Adults with depression n=11 63 64 66-73 75 Dementia n=5 [107][108][109][110][111] Older adults n=5 [33][34][35][36][37] Chronic obstructive pulmonary disease n=4 78 112-114 Multiple sclerosis n=4 81 115-117 Pregnant or postnatal or post-partum women n=4 [38][39][40][41] Adults with various chronic diseases n=3 [118][119][120] Apparently healthy adults n=3 [42][43][44] Anxiety disorders n=3 84 85 121 Cardiovascular disease n=3 80 122 123 Older adults with depression n=4 63 65 74 124 Renal disease n=3 86 125 126 Stroke n=3 21 127 128 Arthritis and rheumatic diseases n=2 82 129 130 Cognitive impairment n=2 77 131 HIV/AIDS n=2 76 132 Post-traumatic stress disorder n=2 133 134 Various mental health disorders n=2 83 135 Fatigue n=1 136 Knee osteoarthritis n=1 129 Neurological disorders n=1 137 Schizophrenia n=1 138 Substance use disorder n=1 79…”
Section: Psychological Distressmentioning
confidence: 99%
“…Groot et al (2016) 14 included 18 studies comparing aerobic exercise with, non‐aerobic or combined exercise, and reported benefits for cognitive function only when intervention included aerobic exercise alone or combined with non‐aerobic exercise. The remaining multicomponent exercise programs include revisions of functional training, 32 , 38 , 39 , 40 and others which combine different types of exercise such as Tai chi, virtual reality, or exergames, yoga, and mind body exercise. 38 , 41 , 42 Only two reviews 40 , 43 failed to report benefits in cognitive function.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining multicomponent exercise programs include revisions of functional training, 32 , 38 , 39 , 40 and others which combine different types of exercise such as Tai chi, virtual reality, or exergames, yoga, and mind body exercise. 38 , 41 , 42 Only two reviews 40 , 43 failed to report benefits in cognitive function. Assorted differences in the exercise protocols make it difficult to identify general guidelines for multicomponent exercise intervention.…”
Section: Resultsmentioning
confidence: 99%
“…61,62 Within the HIIT framework, interventions encompassing the patient's goals and functional demands are critical to recovery and ameliorating neurological symptoms. 61,62 A recent systematic review and meta-analysis by Russ et al 63 found small but positive effects of HIIT for patients with various types of dementia, including improved balance and independence with ADL performance. Integrating functional and meaningful activities into a HIIT framework shows promise for simultaneously meeting physiological and physical goals while producing maximum patient benefit.…”
Section: Cerebrovascular Accidents and Other Neurological Conditionsmentioning
confidence: 99%